2023
DOI: 10.21769/bioprotoc.4654
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Acyl-RAC Method of Isolating Retinal Palmitoyl Proteome for Subsequent Detection through LC-MS/MS

Abstract: Palmitoylation is a unique and reversible posttranslational lipid modification (PTM) that plays a critical role in many cellular events, including protein stability, activity, membrane association, and protein–protein interactions. The dynamic nature of palmitoylation dictates the efficient sorting of various retinal proteins to specific subcellular compartments. However, the underlying mechanism through which palmitoylation supports efficient protein trafficking in the retina remains unclear. Recent studies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…These studies have repeatedly identified many sites of modification that are not positively identified as being palmitoylated by MS. Short-chain acyl modifications to cysteine were not known in the literature and not searched for and hence could not be observed even if present. 24,33,34 The presence of thioester bound acyl-cysteine sites that did not map to known sites of palmitoylation hinted at the existence of short-chain cysteine acylomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have repeatedly identified many sites of modification that are not positively identified as being palmitoylated by MS. Short-chain acyl modifications to cysteine were not known in the literature and not searched for and hence could not be observed even if present. 24,33,34 The presence of thioester bound acyl-cysteine sites that did not map to known sites of palmitoylation hinted at the existence of short-chain cysteine acylomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies characterizing the long-chain cysteine acylome have used a variety of chemical approaches to achieve enrichment. 24,33,34 Unfortunately, these approaches all fail to differentiate between long-chain and short-chain acylation. The ability to either enrich for specific S-acyl modifications, or match specific enriched sites to specific acyl modifications will be key to better understanding of the physiological role of short-chain acyl modifications of cysteine.…”
Section: Discussionmentioning
confidence: 99%